The US-Mexico Border: Asylum, Fear and Trump - Crandall, Russell (Survival (London), 2021)
In his impassioned book The Dispossessed, John Washington vividly charts how the United States (and the West in general) has eviscerated asylum protections for the world's most vulnerable people.